Optimization and comparative analysis of PID and FOPID controller for BLDC motor - P. Vimala; C. R. Balamurugan; A. Subramanian; T. Vishwanath (Institute of Advanced Engineering and Science, 2019)
The FOPID and PID controller are designed to control the speed of the BLDC motor. The parameters , , , λ and µ of these controller are optimized based on genetic algorithm. The optimized coefficients keep in track with zero error signals. The output of the controller is given to the variable dc source which varies the input voltage to the three phase inverter depending on the input signal. The three phase inverter gives the voltage to the BLDC motor which enhances the stability of the system. The effectiveness of the controller is demonstrated by simulation.